The putative cannabinoid receptor GPR55 defines a novel autocrine loop in cancer cell proliferation - Pieiro, R.; Maffucci, T.; Falasca, Marco (2011)
Recently, the orphan receptor G protein-coupled receptor 55 (GPR55) has been proposed as a potential cannabinoid receptor, although controversy remains on its physiological roles. Current evidence suggests a role for GPR55 as a receptor for the lysophospholipid lysophosphatidylinositol (LPI). In this study, we show that GPR55 is expressed in several prostate and ovarian cancer cell lines, both at the mRNA and at the protein level, and that it has a critical role in regulating proliferation and anchorage-independent growth. We further show that GPR55 mediates the effects of LPI in prostate and ovarian cancer cells. Indeed we demonstrate that LPI is able to induce calcium mobilization and activation of Akt and extracellular signal-regulated kinase (ERK)1/2 in these cells and that both pharmacological blockade of GPR55 and its downregulation using specific small interfering RNA strongly inhibits these processes. We further identify an autocrine loop by which LPI is synthesized by cytosolic phospholipase A2, pumped out of the cell by the ATP-binding cassette transporter ABCC1/MRP1, and is then able to initialize cascades downstream of GPR55. All together, these data demonstrate a role of LPI and its receptor GPR55 in cancer cells in activating an autocrine loop that regulates cell proliferation. These findings may have important implications for LPI as a novel cancer biomarker and for its receptor GPR55 as a potential therapeutic target. © 2011 Macmillan Publishers Limited All rights reserved.